Efficacy and Toxicity of Immune -Checkpoint Inhibitors in Patients With Preexisting Autoimmune Disorders - Coureau, Michelle; Meert, Anne-Pascale; Berghmans, Thierry; Grigoriu, Bogdan (Frontiers in Medicine, 2020)
Immunotherapy is an important armamentarium for cancer treatment nowadays. Apart from their significant effectiveness in controlling disease they also generate potential severe immune related adverse effects. Preexistence of immune related conditions may eventually predispose to the development of more severe complication and extreme caution have been taken in treating these patients. We performed a literature review searching for case reports and case series in order to offer evidence-based data for clinical management of these patients. Preexisting serological-only immune abnormalities or presence of a predisposing genetic background does not seem to confer significant risk but existing data is scarce. Most patients with preexistent autoimmune diseases can probably treated with checkpoint inhibitors as they seem to have at least the same response rate as the general cancer population. Under treatment, a significant part of them (at least 30%) can experience a flare of their baseline disease which can sometime be severe. Life-threatening cases seems rare and disease flare can be generally managed with steroids. The volume of available data is more important for rheumatologic diseases than for inflammatory bowel diseases were more caution should be observed. However, it has to be kept in mind that new immune related adverse effects (IrAE) are seen with a similar frequency as the flare of the baseline disease. Both flare-up’s and newly developed IrAE are generally manageable with a careful clinical follow-up and prompt therapy.